Value of examination of the gastric aspirate for the diagnosis of neonatal infection - Yadav, Meetu; Gupta, Raksha; Singh, Jasbir; Saraswath, Sameer; Nagaraj, Niranjan; Bana, Sailen Kumar (International Journal of Contemporary Pediatrics, 2018)
Background: Infections in early neonatal period are one of the important factors responsible for high perinatal mortality and neonatal morbidity in developing countries. This study aims to know the role of Gastric aspirates cytology in predicting the early septicemia in newborn babies. Methods: The study will be conducted on 100 neonates with suspected septicemia and 50 normal neonates admitted to neonatology section. Gastric aspirate sample was collected for sepsis screening of neonates. All the collected data was tabulated and statistically analysed by using SPSS 2.0 software. Results: The sensitivity of gastric aspirate cytology is 50%, specificity 65.62%, positive predictive accuracy 47.6%, negative predictive accuracy of 67. 7%. The relationship between gastric aspirate cytology and maternal risk factors was found to be statistically not significant except PIH and PROM in which association is significant. The relationship of prolonged rupture of membranes with gastric aspirate cytology was found to be highly statistically significant. Conclusions: The chances of positivity of gastric aspirate increase as the duration of rupture of membranes increased. Gastric aspirate had high percentage of specificity and negative predictive accuracy. No specific and significant correlation between positive gastric aspirate cytology and rural/urban area, birth weight, sex, gestation, prolong labour, meconium stained amniotic fluid, mode of delivery was found.